Keski- ja korkeatehoisen kestävyystyyppisen intervalliliikunnan vaikutus nuorten inhibitioon pitkäkestoisen istumisen aikana – VERNA-tutkimus - Vahteri, Minna (2024)
Vahteri, M. 2024. Effects of moderate- and high-intensity interval exercise on adolescents’ inhibition during prolonged sitting – VERNA-study. University of Jyväskylä, Master’s thesis in Sports and Exercise Medicine, 80 pp., 3 appendices.